2018
DOI: 10.1055/s-0043-123467
|View full text |Cite
|
Sign up to set email alerts
|

Underwater endoscopic mucosal resection: a new endoscopic method for resection of rectal neuroendocrine tumor grade 1 (carcinoid) ≤ 10 mm in diameter

Abstract: Background and study aims  Rectal neuroendocrine tumors grade 1 (NET G1; carcinoid) ≤ 10 mm in diameter often extend into the submucosa, making their complete histological resection difficult using endoscopic techniques. Endoscopic submucosal resection with a ligation device (ESMR-L) and endoscopic submucosal dissection (ESD) are commonly used to overcome these difficulties. We also previously reported that underwater endoscopic mucosal resection (UEMR) could facilitate resection of rectal NET G1. This study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 9 publications
0
25
0
Order By: Relevance
“…The 6-month follow-up colonoscopy in non-R0 resection patients showed no residual tumor. 109 Transanal endoscopic microsurgery (TEM) may also be considered for <20-mm lesions superficial to the muscularis propria. In this procedure, a full-thickness resection can be performed transanally and the defect closed by a continuous running suture.…”
Section: Surgical Managementmentioning
confidence: 99%
“…The 6-month follow-up colonoscopy in non-R0 resection patients showed no residual tumor. 109 Transanal endoscopic microsurgery (TEM) may also be considered for <20-mm lesions superficial to the muscularis propria. In this procedure, a full-thickness resection can be performed transanally and the defect closed by a continuous running suture.…”
Section: Surgical Managementmentioning
confidence: 99%
“…In contrast to standard EMR, UEMR does not require a submucosal injection because the buoyancy effect on the adenoma-bearing mucosa raises it from the deeper muscularis propria. During the past 6 years, about 30 studies on UEMR were published, and they indicated the usefulness of UEMR for large sessile colon polyps, 11 polyps in difficult locations, 12 13 14 duodenal non-ampullary adenomas, 15 neuroendocrine tumors, 16 17 and recurrent colorectal polyps 18 . However, only three reports compared clinically relevant outcomes of colorectal UEMR and standard EMR.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, other techniques for endoscopic resection of rectal NET were introduced. Underwater EMR (UEMR) is a novel modified EMR method that can promote the lifting and floating away of a submucosal tumor from muscularis propria by buoyancy 25 . In a retrospective study analyzing small rectal NETs (≤ 10 mm), UEMR achieved 86.1% of histologic complete resection rate comparable to ESD.…”
Section: Discussionmentioning
confidence: 99%